IMPLEMENTASI SISTEM INFORMASI KESEHATAN BERBASIS KADER POSYANDU UNTUK DIGITALISASI DATA KESEHATAN - Dodi Syaripudin; Faldy Irwiensyah; Rusdi Doviyanto; Zuhri Halim (Yayasan Nusa Cendekia Global, 2026)
Posyandu plays a crucial role in maternal and child health monitoring; however, manual recording systems using KIA/KMS books often lead to data inconsistency, physical damage risks, and delays in reporting health indicators such as stunting. This community service activity was carried out through an approach focused on the development and implementation of a health information system based on Posyandu cadres. This study aims to design and implement a digital health information system to transform data management processes at the Posyandu level to be more accurate, efficient, and integrated. This research employs the Research and Development (R&D) method with the Waterfall development model. The system design is modeled using the Unified Modeling Language (UML), including use case, activity, and class diagrams. Testing was conducted using Black Box Testing for functional validation and User Acceptance Test (UAT) to measure the level of user acceptance. The results show that the developed information system is 100% functional according to technical specifications. UAT testing among Posyandu volunteers (kader) indicated a satisfaction rate of 88%, categorizing the system as Highly Acceptable. Data digitalization through this system significantly accelerates the data recapitulation process and minimizes input errors, thereby supporting more targeted medical decision-making at the Community Health Center (Puskesmas) level.